Mechanism and In Vivo Evaluation: Photodynamic Antibacterial Chemotherapy of Lysine-Porphyrin Conjugate - Xu, Zengping; Gao, Yuxiang; Meng, Shuai; Yang, Baochen; Pang, Liyun; Wang, Chen; Liu, Tianjun (Frontiers in Microbiology, 2016)
We previously reported lysine-porphyrin conjugate 4i, which had potent photosensitive antibacterial effect on clinical isolated Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa) bacterial strains. The aim of this paper is to evaluate the mechanism of photodynamic antibacterial chemotherapy of 4i (4i-PACT) in vitro and the treatment effect in vivo. Atomic force microscopy (AFM) revealed 4i-PACT could effectively destroy bacterial membrane and wall, making the bacterial content leakage, which was confirmed by dual fluorescent staining with acridine orange/ethidium bromide (AO/EB) and absorbance at 260 nm, agarose gel electrophoresis indicated 4i-PACT could damage genomic DNA. The results combined AFM and DNA electrophoresis revealed why the bacterial strains had no resistance to 4i-PACT. Wound healing in rat model with mixed bacteria infected wounds showed the efficiency of 4i-PACT was light-dose dependent. These results showed 4i-PACT had promising bactericidal effect both in vitro and in vivo.